Inability of thymus cells from newborn donors to restore transplantation immunity in athymic mice. - Pierpaoli, W (1975)
Passive transfer of thymus cells from congenic donors to athymic mice reconstitutes the recipient's capacity to reject allogeneic skin grafts, provided the donor is immunologically mature and the number of thymus cells from the adult donor is high enough. Passive transfer of thymus cells from adult allogeneic donors induces a mild to severe graft-versus-host disease and the grafts are retained until death. These results are interpreted on the basis of recent findings on the endocrine conditions of congenitally athymic mice and on the previous data on the hormone dependence of thymus cells to acquire immunocompetence. It is proposed that a normal host environment is a prerequisite for the thymus-derived cells to perform in cell-mediated immune reactions.